Implementasi E-Commerce Telur Asin AS (Agus Sahli) Berbasis Website (Studi Kasus Desa Rejagung Trangkil Pati) - Evi Khaulida; Tri Listyorini; Endang Supriyati (Yayasan Literasi Sains Indonesia, 2023)
Website design for the implementation of E-Commerce implementation of selling salted eggs typical of Rejoagung Trangkil Pati village to analyze online marketing utilization activities for selling salted eggs in Pati district. Previous sales used conventional methods, selling in shops and deposits at several shops in Pati Regency. Some producers have utilized online media but still have limited knowledge in using online media. In this research, the researcher collected data using interviews, with the help of questionnaires, observation and documentation. The method used is waterfall system development. The results of this research are that producers have carried out online advertising, salted egg producers have utilized online media including websites, blogs and social media. Online sales use the payment gateway payment facility, namely the sandbox version of Midtrans. This system is also equipped with WhatsApp notifications to provide information regarding updates on purchasing salted eggs. This sales system is also equipped with API Raja Ongkir, this is useful for checking expeditions and shipping costs for sending salted eggs.